2012
DOI: 10.1161/jaha.112.003152
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Serum C‐Peptide Levels Predict Cardiovascular and Overall Death in Nondiabetic Adults

Abstract: BackgroundInsulin resistance, characterized by hyperinsulinemia and normal or elevated serum glucose, is an established precursor to diabetes and cardiovascular disease. Despite fasting serum C‐peptide levels being an accurate and stable marker of endogenous insulin production used in patients with diabetes, it is unknown whether C‐peptide could serve as a marker of insulin resistance and predict outcomes in patients without diabetes.Method and ResultsThis is a retrospective cohort study using data from the NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
66
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 47 publications
5
66
0
2
Order By: Relevance
“…The pro-atherogenic effects are doserelated and produce increased chemotactic activity, proliferation of aortic smooth muscle cells, and activation of key inflammatory mediators involved in atherogenic processes, including the NFκ B factor (Lebbherz and Marx, 2013). Positive correlations of high C-peptide levels with cardiovascular deaths are stronger than fasting glucose levels, homeostatic model assessment index or insulin in adult non-diabetics (Patel et al, 2012;Min and Min, 2013). High fasting C-peptide concentrations are also related to risk of liver and biliary tract cancer and low cognition scores in middle age subjects with insulin resistance (Pedersen et al, 2012;Aleksandrovaet et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The pro-atherogenic effects are doserelated and produce increased chemotactic activity, proliferation of aortic smooth muscle cells, and activation of key inflammatory mediators involved in atherogenic processes, including the NFκ B factor (Lebbherz and Marx, 2013). Positive correlations of high C-peptide levels with cardiovascular deaths are stronger than fasting glucose levels, homeostatic model assessment index or insulin in adult non-diabetics (Patel et al, 2012;Min and Min, 2013). High fasting C-peptide concentrations are also related to risk of liver and biliary tract cancer and low cognition scores in middle age subjects with insulin resistance (Pedersen et al, 2012;Aleksandrovaet et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the results of previous studies and suggest a role for C-peptide in predicting increased risk of cardiovascular events and death regardless of the presence of diabetes. [6][7][8][9][10][11][12] Among patients with type 2 diabetes, C-peptide level has been reported to be significantly correlated with intima-media thickness, 10 triglyceride level, high-density lipoproten cholesterol levels, leptin levels and BMI. 8 The Wisconsin Epidemiologic Study of Diabetic Retinopathy followed 1007 individuals with older-onset diabetes over 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…12 A community-based survey of adults aged 30 years and older with normal glucose tolerance found that serum C-peptide levels were quantitatively associated with the signs and symptoms of metabolic syndrome X, including BMI, triglyceride level, high-density lipoprotein cholesterol level and blood pressure. 7,9 The recent study by Patel and colleagues 11 found that C-peptide levels were superior to other known indices (e.g., serum insulin, the homeostatic model assessment of insulin resistance, and the quantitative insulin sensitivity check index) in predicting all-cause and cardiovascular-related mortality among adults without diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when C-peptide levels were analyzed in 5153 non-diabetic adults between 40 and 74 years of age, individuals with the highest C-peptide measurements (≥0.984 nmol/L = 2.95 ng/ml, (27)) had a 60% increase in the adjusted hazards of cardiovascular death compared to those with the lowest (≤0.418 nmol/L = 1.25 ng/ml). This trend persisted in risk for cerebrovascular disease, ischemic heart disease, myocardial infarction, and overall mortality (29). C-peptide induces proliferation of smooth muscle cells potentially leading to the development of atherosclerotic lesions (30).…”
Section: Discussionmentioning
confidence: 95%